PERLINDUNGAN HUKUM TERHADAP ANAK DI BAWAH UMUR AKIBAT PUTUSNYA PERKAWINAN KARENA PERCERAIAN (STUDI PADA MASYARAKAT BATAK TOBA KRISTEN DI MEDAN) - ERNAWATI BR. SITORUS (PREMISE LAW JURNAL, 2016)
A broken marriage of a divorce does not cause the relationship between the man and his ex-wife to break off, the same is true to their children. The result of his research shows that in general in the Batak Toba community, the mirror is reised by their father because Batak Toba community adheres to patrilineal. But, if the mirror still suckles, he has to be under his mother’s custody until he is 2 to 3 years old and can be ‘sirang susu’ (separated breastfeeding). As time goes by, today mirror is free to determine who will be his guidance. The obstacle in the implementation of the divorced parents responsibility is that there is no law which regulates the custody of the mirror from divorced parents. Besides that, the court’s verdict is difficult to be practiced because there is no sanction imposed upon parents, especially their father, who neglects their responsibility. Parents’ negligance is influenced by some factors such as economic factor, both parents remary, phychological factor, and the mother is able to take care of the minor. Keywords: Legal Protection, Minor, Batak Toba, Christianity